Prevalence, drug resistance, molecular typing and comparative genomics analysis of MRSA strains from a tertiary A hospital in Shanxi Province, China - Hou, Zhuru; Xu, Benjin; Liu, Ling; Yan, Rongrong; Zhang, Jinjing; Yin, Jiaxin; Li, Peipei; Wei, Jianhong (Frontiers in Microbiology, 2023)
Staphylococcus aureus (S. aureus) is an important zoonotic pathogen that causes a high incidence rate and mortality worldwide. This study investigated the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) strains in a tertiary A hospital in Shanxi Province, China, in order to determine the major epidemic clones as well as their antibiotic resistance and virulence characteristics. A total of 212 S. aureus strains were collected in this hospital, and were subjected to antimicrobial susceptibility testing, detection of virulence genes, resistance genes, and efflux pump genes. Among them, 38 MRSA strains were further subjected to detection of biofilm genes, assessment of biofilm formation ability, MLST, spa typing, SCCmec typing, and phylogenetic analysis. The majority of S. aureus strains came from the neonatology department, with secretions and purulent fluid being the main source of samples. The strains showed high resistance to penicillin (98.11%), erythromycin (64.62%) and clindamycin (59.91%), while being sensitive to vancomycin and linezolid. The detection rates of efflux pump genes and resistance genes were high, and there was a significant correlation between resistance gene types and phenotypes, with mecA showing a close correlation with oxacillin. The detection rates of virulence genes and the toxin gene profiles of MSSA and MRSA strains showed significant differences. And the detection rate of biofilm genes in MRSA strains was relatively high, with 13.16% of MRSA strains showing strong biofilm formation ability. The most common epidemic clone of MRSA was ST59-SCCmecⅣ-t437, followed by ST59-SCCmecⅤ-t437. The former had a higher detection rate of resistance genes and a stronger biofilm formation ability, while the latter had a higher positive rate for pvl gene and stronger pathogenicity, making it more likely to cause systemic infections. Phylogenetic analysis showed that all MRSA strains in this study clustered into three major branches, with distinct differences in antibiotic resistance and virulence characteristics among the branches. ST59-MRSA strains from different species showed consistency and inter-species transmission, but there were differences among ST59-MRSA strains from different geographical locations. In general, most MSSA and MRSA strains exhibited multidrug resistance and carried multiple resistance genes, virulence genes, and biofilm formation genes, warranting further research to elucidate